Long Noncoding RNA lnc-TSSK2-8 Activates Canonical Wnt/β-Catenin Signaling Through Small Heat Shock Proteins HSPA6 and CRYAB - Fa, Jingjing; Zhang, Xiaoqing; Zhang, Xiaoping; Qi, Ming; Zhang, Xingyu; Fu, Qihua; Xu, Zhuoming; Gao, Yunqian; Wang, Bo (Frontiers in Cell and Developmental Biology, 2021)
Congenital heart defects (CHDs) are the most common birth defects worldwide. 22q11.2 deletion syndrome is the most common microdeletion disorder that has been frequently associated with conotruncal malformations. By now, the dosage-sensitive gene TBX1 has been adopted as the major pathogenic gene responsible for 22q11.2 deletion, which is regulated by canonical Wnt/β-catenin signaling pathway in heart outflow tract development. Here, we report the long noncoding RNA (lncRNA) lnc-TSSK2-8, which is encompassed in the 22q11.2 region, that can activate canonical Wnt/β-catenin signaling by protecting β-catenin from degradation, which could result from decreased ubiquitination. Such effects were mediated by two short heat shock proteins HSPA6 and α-β-crystallin (CRYAB), whose expression was regulated by lnc-TSSK2-8 through a competing endogenous RNA (ceRNA) mechanism. In clinical practice, the pathogenesis of copy number variation (CNV) was always attributed to haploinsufficiency of protein-coding genes. Here, we report that the 22q11.2 lncRNA lnc-TSSK2-8 significantly activated canonical Wnt/β-catenin signaling, which has major roles in cardiac outflow tract development and should act upstream of TBX1. Our results suggested that lncRNAs should contribute to the etiology of CNV-related CHD.